Sustainable Utilization of Agricultural By-Products: in vivo investigation of the antidiarrheal potential of Litchi chinensis seed extract - Mustakin Ahmed Shohel; Md. Humayan Kabir; Ivvala Anand Shaker; Sumaiya Siddika; Sheikh Arafat Rahman; Sumaiya Siddiquea; Nirmal Chandra Mahat; Tarique Muhammad Tawabul Islam; Md. Abul Kashem Tang (Journal of Pharmacopuncture)
Objectives: Diarrheal diseases remain a significant global health concern, with rising resistance to traditional pharmaceutical treatments. Litchi chinensis, a tropical fruit, is known for its medicinal properties, but its seed, which is often discarded as waste, has not been extensively studied for its potential health benefits. This study investigates the antidiarrheal effects of L. chinensis seed extract (LCSE). Methods: Ethanolic extract was prepared from dried, powdered L. chinensis seeds. Acute oral toxicity was conducted by administering a single 2,000 mg/kg dose to female Swiss albino mice. Mice were divided into five groups (control, positive control with Loperamide, and test groups receiving 100, 200, and 400 mg/kg of LCSE) for the antidiarrheal assay. Diarrhea was induced with castor oil, and parameters such as onset of diarrhea, fecal output, gastrointestinal motility, and enteropooling were measured. The statistical analysis was conducted in GraphPad Prism version 10.1.2 using one-way ANOVA followed by a Dunnett multiple comparison test. Results: L. chinensis seed extract (LCSE) significantly (p < 0.001) delayed the onset of diarrhea, reduced the frequency of defecation, and decreased fecal weight in the castor oil-induced diarrhea model at all doses (100, 200, and 400 mg/kg). Additionally, LCSE significantly (p < 0.001) reduced total and wet fecal output, inhibited gastrointestinal motility (p < 0.001) in the charcoal meal test, and notably (p < 0.001) decreased the volume and weight of intestinal contents in the enteropooling assay. The in vivo antidiarrheal index (ADI) showed a dose-dependent increase, with the highest ADI recorded at 400 mg/kg (189.42%), slightly surpassing the standard drug, loperamide (160.14%). Conclusion: The finding supports the antidiarrheal potential of LCSE holds potent antidiarrheal properties, positioning it as a promising, sustainable alternative to modern medications.